Persepsi Siswa terhadap Lingkungan Sekolah di SMK Taruna Padang - Sabrina, Sabrina; Jasrial, Jasrial (Lembaga Yasin AlSys, 2024)
This research was motivated by the school environment which was not as good as expected by Taruna Padang Vocational School. The aim of this research is to obtain information regarding students' perceptions of the school environment at Taruna Padang Vocational School, which is seen from the aspects of school facilities, learning resources, learning media, teacher-student relationships and student-student relationships. Therefore, the problem that will be studied in this research is,